IMPLEMENTASI DIVERSI DALAM MENYELESAIKAN TINDAK PIDANA ANAK DI TINGKAT KEJAKSAAN NEGERI SIBOLGA - Ferdinan P L Tobing; Emilda Firdaus; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Children are gifts or entrusted by God to every parent who is part of the younggeneration of the nation's successors who must be protected. The effort to protectchildren facing the law is through a legal restorative approach carried out bymeans of diversion. Diversion is the transfer of child case processes from criminaljustice processes to processes outside the criminal court. At the level ofinvestigation, prosecution and examination of child cases in the district court,diversion must be sought, this is stated in article 7 paragraph (1) of the ChildCriminal Justice System Act. The purpose of writing this thesis, namely: First, Tofind out the implementation of diversion in the Sibolga District Prosecutor'sOffice. Second, to find out the inhibiting factors for the implementation ofdiversion in the Sibolga District Prosecutor's Office. Third, Untik knows theefforts of the Prosecutor's Office to overcome the inhibiting factors for theimplementation of diversion in the Sibolga District Prosecutor's Office.This type of research can be classified in this type of sociological juridicalresearch, because this research author directly conduct research on the locationsor places studied in order to give a complete and clear picture of the issuesexamined. This research was conducted at the Sibolga District Prosecutor'sOffice, whereas the sample population is a whole party with regard to the issuesexamined in this study, the data source used, primary data, secondary data anddata tertiary, technical data collectors in this study with interviews and literaturestudy.From the results of research and discussion it can be concluded that,First, the implementation of diversion in resolving child crime at the SibolgaDistrict Attorney level has not been maximized. Second, the inhibiting factors ofdiversion efforts at the Sibolga District Prosecutor's Office are the lack of thenumber of public prosecutors, the paradigm of the public prosecutor, the lack ofcooperation between institutions and the parties, and the work area of the SibolgaDistrict Attorney consisting of 2 (two) jurisdiction . Third, the public prosecutor'sefforts in overcoming the inhibiting factors are by increasing the number of childprosecutors, conducting training and education on diversion and seeking goodcooperation between institutions.Keywords: Implementation – Diversion - Child